First record of the genus Zethus Fabricius, 1804 (Hymenoptera: Vespidae, Eumeninae) from China with description of a new species - Nguyen, Lien Thi Phuong; Xu, Zai-Fu (Zootaxa, 2017)
The genus Zethus Fabricius, 1804, is newly recorded from China. The male of Zethus malayanus Gusenleitner, 2010 is described and figured for the first time. Zethus nanlingensis Nguyen & Xu, sp. nov. (South China, Guangdong) is described and figured.